High energy blow up for two-dimensional generalized exponential-type Boussinesq equation. (August 2020) - Guo, Siyan; Yang, Yanbing
Abstract: A finite time blow up result for the Cauchy problem of two-dimensional generalized Boussinesq-type equation with exponential type source term is considered in this paper. Based on an adapted concave method, we derive a sufficient condition on initial data leading to the arbitrarily positive initial energy finite time blow up.